2022
DOI: 10.3390/ijerph192416423
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Students’ Mental Health during the COVID-19 Pandemic: The Impact of Coping Strategies, Sense of Coherence, and Social Support

Abstract: Young people and women seem to suffer more from social restrictions due to the COVID-19 pandemic than do others. Findings from pre-pandemic surveys identified students as a specific risk group for developing anxiety and depressive symptoms. Recent studies have indicated that students especially denoted a decrease in mental health during the pandemic. In a sample of n = 1938 university students (67.6% female), we investigated protective factors that are associated with mental health (defined as the absence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…This is similar to previous research, which explains that boys with sufficient knowledge of coping with emotional disturbances have a lower likelihood of dying by suicide [86]. Despite these findings, other studies have shown that adolescent boys have better coping strategies with respect to identifying mental health and did not experience significant depression when facing social restrictions during the COVID-19 pandemic [87]. Our study also found that unemployed adolescents were 1.61 times more likely to experience behavioral and/or emotional disturbances than employed adolescents.…”
Section: Adolescent = Subset(ssn_under26 Age<20) and (Age >9))supporting
confidence: 89%
“…This is similar to previous research, which explains that boys with sufficient knowledge of coping with emotional disturbances have a lower likelihood of dying by suicide [86]. Despite these findings, other studies have shown that adolescent boys have better coping strategies with respect to identifying mental health and did not experience significant depression when facing social restrictions during the COVID-19 pandemic [87]. Our study also found that unemployed adolescents were 1.61 times more likely to experience behavioral and/or emotional disturbances than employed adolescents.…”
Section: Adolescent = Subset(ssn_under26 Age<20) and (Age >9))supporting
confidence: 89%